A century of macro-financial linkages. Issue 4 (7th November 2016) - Abildgren, Kim
Abstract : Purpose: The recent international financial crisis and the subsequent Great Recession has underlined the need to gain a better understanding of the linkages between financial factors and the real economy. The purpose of this paper is to explore the contributions of financial shocks to macroeconomic fluctuations in Denmark, USA and Canada over the past century. Design/methodology/approach: The paper compiles a new data set with break-adjusted quarterly time series of real gross domestic product (GDP) and six other key macroeconomic indicators for the three countries since 1921. It then explores the time-variation of macro-financial linkages by estimating structural vector-autoregressive models separately for three sample periods: 1921-1949, 1950-1979 and 1980-2014. Findings: For all three countries, there seems to have been a non-trivial contribution from financial shocks to volatility in output and unemployment in all sample periods, even in the period 1950-1979, which was characterised by tight regulation of the financial sector and widespread financial stability. These findings underscore the general importance of financial factors to macroeconomic fluctuations. Originality/value: The paper is the first to offer regression-based estimates of quarterly real GDP for Denmark for 1921-1947. As a result, quarterly figures for real GDP are now available for Denmark for the entire period 1921-2014. Such long-span time series of quarterly real GDP do not exist for any other European countries.